Disability and Demonstrating Christian Commitment. (13th December 2013) - Jarman, Andrea Loux
<x content-type="archive" xml:space="preserve">Abstract</x> Community lies at the heart of both church and school life in the Church of England. In some areas, church communities are sustained by families who choose to attend a particular church based on the quality of the church school in its parish. Many Voluntary Aided Church of England schools (church schools) give priority admission to parents on the basis of faith in the oversubscription criteria of their admission arrangements. While the Church stresses inclusiveness in its recommendations regarding admissions policies to church schools, where a church school is very popular and oversubscribed arguably priority must be given to parents of the faith in the school's catchment area. Otherwise parishioner children whose families regularly attend church could fail to be admitted to their local church school because of competition for places.